Comparison of Chromosomal Microarray Analysis and Noninvasive Prenatal Testing in Pregnant Women with Fetal Ultrasonic Soft Markers - Hu X; Hu Y; Wang H; Yu C; Zheng J; Zhang H; Zheng J (Dove Medical Press, 2024)
Xianqing Hu,1 Yanjun Hu,1 Hai Wang,2 Caicha Yu,3 Jiayong Zheng,2 Hongping Zhang,1 Jianqiong Zheng1 1Department of Obstetrics and Gynecology, The Third Clinical Institute Affiliated to Wenzhou Medical University, Wenzhou People's Hospital, Wenzhou Maternal and Child Health Care Hospital, Wenzhou, People's Republic of China; 2Department of Fetal Medicine and Prenatal Diagnosis, The Third Clinical Institute Affiliated to Wenzhou Medical University, Wenzhou People's Hospital, Wenzhou Maternal and Child Health Care Hospital, Wenzhou, People's Republic of China; 3Department of Ultrasonography, The Third Clinical Institute Affiliated to Wenzhou Medical University, Wenzhou People's Hospital, Wenzhou Maternal and Child Health Care Hospital, Wenzhou, People's Republic of ChinaCorrespondence: Jianqiong Zheng; Hongping Zhang, Email zjq1980120@163.com; 413599343@qq.comObjective: This study aimed to assess the utility of chromosomal microarray analysis (CMA) and noninvasive prenatal testing (NIPT) in detecting clinically significant chromosomal abnormalities among fetuses presenting ultrasonic soft markers (USMs).Methods: A retrospective observational study, spanning from January 1, 2019, to September 30, 2022, enrolled 539 singleton pregnant women with fetal USMs at our center. Of these, 418 cases (77.6%) underwent NIPT, while 121 cases (22.4%) opted for invasive prenatal diagnosis post-appropriate genetic counseling. Cases with high-risk NIPT results proceeded to invasive prenatal diagnosis, where conventional karyotyping and CMA were concurrently performed. Further stratification was done based on the number of USMs, classifying cases into single-USM and multiple-USM groups.Results: Of the 24 cases (4.5%) exhibiting abnormal findings, 17 presented numerical chromosomal abnormalities, 2 featured clinically significant copy number variations (CNVs), 3 showed variants of unknown significance (VOUS), 1 displayed LOH, and 1 exhibited chromosome nine inversion. Notably, 18 cases (75%) theoretically detectable by karyotyping (eg, sizes above 10Mb) and 16 cases (66.7%) detectable by NIPT for five common aneuploidies were identified. Six submicroscopic findings (25%) were exclusively detectable by CMA. The predominant clinically relevant aberrations were observed in the thickened nuchal-translucency (TNT) group (9/35, 25.7%), followed by the multiple soft markers group (3/32, 9.3%). In the NIPT group, the false positive rate was 1.22%, and the false negative rate was 0%.Conclusion: The prevalence of chromosome aneuploidy exceeded that of submicroscopic chromosomal imbalance in pregnant women with fetal USMs. NIPT demonstrated efficacy, particularly for soft markers like echogenic intracardiac focus. However, for those with TNT and multiple soft markers, invasive prenatal diagnosis, including CMA testing, is recommended as the primary investigative approach.Keywords: chromosomal microarray analysis, karyotype, noninvasive prenatal testing, ultrasonic soft markers, prenatal diagnosis